Studying trait-playfulness, time spent with physical activity, and athletic identity among self-ascribed athletes and non-athletes - Brauer, Kay; Donhauser, Johanna E.; Proyer, René T. (Frontiers in Sports and Active Living, 2025)
Adult playfulness is an individual difference variable that describes how people (re)frame situations in a way that they are experienced as entertaining, and/or intellectually stimulating, and/or personally interesting. Playfulness relates to indicators of mental and physical health, but its role among athletes is yet understudied. In our study, we provide initial findings on playfulness with regard to self-reported athleticism by (a) comparing expressions in four facets of playfulness (Other-directed, Lighthearted, Intellectual, and Whimsical types) between athletes (n = 205) and non-athletes (n = 209), and (b) testing associations with subjective impressions of athletic identity (i.e., the degree of one's identification of being an athlete) and reports of time spent with physical activity. Our findings showed that (a) there is measurement invariance of playfulness among the groups, (b) athletes yield higher expressions of Lighthearted playfulness (g = 0.31), and among athletes, playfulness goes along with more time spent participating in physical activity whereas it was unrelated to athletic identity; among non-athletes, Other-directed playfulness related to perceiving oneself as being athletic. We discuss our findings regarding implications for leisure and performance-related outcomes and in line with the literature noting the important role of playfulness in sports.